ANALISIS PENGUJIAN KEKUATAN TARIK DAN UJI KEKERASAN TERHADAP PENGELASAN GTAW PADA SAMBUNGAN KAMPUH MODEL X DENGAN VARIASI MEDIA PENDINGIN PADA BAJA ST60 - Akhmad Vaniludin; marsono marsono; duwi leksono edy (Jurnal Teknik Mesin dan Pembelajaran, 2023)
This research has a purpose to find out the value of the tensile strength and hardness of GTAW welding result in ST60 steel double V joint and cooling media variation water, oil SAE20w-50, air. From the research result the highest tensile strength value uses a variation air cooling media, which is 752,33 MPa. The lowest tensile strength value uses a variation of the water cooling media, which is 709,90 MPa.while using a variation of the oil SAE20w-50 cooling media is 71535. The highest hardness value uses a variation of the water cooling media , which is 244,83 HVN. The lowest hardness value uses a variation of the air cooling media, which is 216,9 HVN. While using a variation oil SAE 20w-50 cooling media is 240,93 HVN.